The Role of School Supervisor from the Point of View of Home Economics Teachers in Reality and Hoped - Al-Anzi, Norah (DIRASAT: EDUCATIONAL SCIENCES, 2021)
This study aims at identifying the point of view of home economic teachers to the role of school supervisor in reality and hoped in Farwaniya at Kuwait The sample consisted of (29) teachers of home economics in Farwaniya governorate at Kuwait which selected through comprehensive screening to home economic teachers who taught in 1st semester of scholastic year 2016/2017. The researcher used an interview as a tool to collect data, the study unveiled that there were (11) roles for school supervisor include guidance to enhance education, enhance teachers competencies, curriculum analysis, evaluation, and cope some administrative tasks. As well as the study unveiled that there were (8) roles for school supervisor in the future include developing education, exchange expertise, assisting teacher in self-development, achieving quality, in addition to curriculum analysis, evaluation, and cope some administrative tasks.